2015
DOI: 10.1002/ijc.29548
|View full text |Cite
|
Sign up to set email alerts
|

Alpha fetoprotein mediates HBx induced carcinogenesis in the hepatocyte cytoplasm

Abstract: Although tumor-associated fetal protein AFP has demonstrated utility as a clinical tumor marker, the significance of intracellular AFP is still unclear. The aim of this study was to explore the role of cytoplasmic AFP during HBx induced carcinogenesis, which had not previously been recognized; 614 HCC patients were analyzed for correlation of HBV infection with AFP level, and much higher AFP levels were found in HBsAg positive patients. Tumor tissue specimens from 20 HCC patients were used for analysis of AFP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 43 publications
2
53
0
Order By: Relevance
“…The authors concluded that HBx-induced CyAFP expression promoted the malignant transformation of liver cells via the activation of PI3K/ mTOR signaling. As demonstrated in the above discussions, CyAFP is associated with downregulation of GADD153 through binding to RAR and disruption of its nuclear transpassage; this resulted in the failure of GADD153 gene activation [58]. As shown above, transfected HBx promoted expression of the CyAFP which serves as an active agent in liver carcinogenesis.…”
Section: Cyafp Involvement In Intracellular Signaling and Regulationmentioning
confidence: 88%
“…The authors concluded that HBx-induced CyAFP expression promoted the malignant transformation of liver cells via the activation of PI3K/ mTOR signaling. As demonstrated in the above discussions, CyAFP is associated with downregulation of GADD153 through binding to RAR and disruption of its nuclear transpassage; this resulted in the failure of GADD153 gene activation [58]. As shown above, transfected HBx promoted expression of the CyAFP which serves as an active agent in liver carcinogenesis.…”
Section: Cyafp Involvement In Intracellular Signaling and Regulationmentioning
confidence: 88%
“…Under the influence of HBx transcriptional activities in the cytoplasm, RAR may also promote hepatocarcinogenesis by interacting with other proteins such as AFP. It was recently shown that interaction of HBx-induced AFP with RAR resulted in perturbed RAR signalling pathway, leading to repression of growth arrest and DNA damage 45 α (GADD45 α ) protein expression [107]. GADD45 α is an 18.4 kDa RNA-binding acidic protein that is expressed in response to DNA damage for repairing and induction of apoptosis by inhibiting G2/M transition of cell cycle.…”
Section: Hbv-induced Hcc Hepatoepigenetic Alterationsmentioning
confidence: 99%
“…GADD45 α is an 18.4 kDa RNA-binding acidic protein that is expressed in response to DNA damage for repairing and induction of apoptosis by inhibiting G2/M transition of cell cycle. Downregulation of GADD45 α in HCC was associated with uncontrolled HBV-infected hepatocytes growth and hepatocarcinogenesis, suggesting its effects in allowing the cells to evade senescence and apoptosis [104, 107]. Although the role of GADD45 α in promoting instability through DNA demethylation has been reported previously, it has not been explored in HBV-induced HCC and therefore warrants investigation [108, 109].…”
Section: Hbv-induced Hcc Hepatoepigenetic Alterationsmentioning
confidence: 99%
“…Circulating AFP acts as a growth regulator during oncogenic growth and tumor progression, and is considered a diagnostic and prognostic tumor marker [13]. In recent years, remarkable progress has been made in determining the biological role of cytoplasmic AFP as a signal molecule: aberrantly elevated AFP disturbs the normal signaling network and shows a strong association with the high mortality rate of HCC [47]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the caspase-3 cascade and the tumor necrosis factor (TNF)-related apoptosis inducing ligand (TRAIL) induce apoptosis is virtually abolished in the presence of AFP [5, 9]. Our previous research has shown the potential association of AFP levels with HBV infection and revealed a hitherto undiscovered role for cytoplasmic AFP in mediating HBV-induced hepatocyte carcinogenesis [7]. Given that cytoplasmic AFP has been defined as a growth-promoting molecule, AFP gene silencing would be beneficial for therapy of HCC patients.…”
Section: Introductionmentioning
confidence: 99%